2009
DOI: 10.1016/j.egypro.2009.02.304
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder acceptance of carbon capture and storage in Germany

Abstract: This paper presents the results of a collaborative project on public acceptance of Carbon Capture and Storage (CCS) in Germany, commissioned by the German Federal Ministry of Economics and Technology (BMWi). The project "Socio-economic Research on Acceptance of CCS" (April 2006 to March 2008) analyzed various aspects of public acceptance of CCS mainly in the national context of Germany. It was the first project to handle this subject matter. Public acceptance is one of the crucial factors for the implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The major concern was the energy penalty associated with CCS and its impact on the long-term supply of coal. The study by Fischedick et al (2009) in Germany concluded that government, industry and energy experts mainly adopt a neutral or positive view of CCS, while most environmental NGOs reject it.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The major concern was the energy penalty associated with CCS and its impact on the long-term supply of coal. The study by Fischedick et al (2009) in Germany concluded that government, industry and energy experts mainly adopt a neutral or positive view of CCS, while most environmental NGOs reject it.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Yet despite proponents communicating the potential of CCS, many people worldwide have little-to-no awareness or knowledge of the technology (European Commission 2011). Studies from Australia (Ashworth et al 2009), Canada (IPAC-CO2 2012a, 2012bSharp, Jaccard, andKeith 2009), France (Ha-Doung, Nadaï, andCampos 2009), Germany (Fischedick et al 2009), Japan (Itaoka et al 2009;Itaoka, Saito, and Akai 2005), the Netherlands (de Best-Waldhober, Daamen, and Faaij 2009;de Best-Waldhober et al 2011;de Coninck and Huijts 2005;Paukovic, Brunsting, and de Best-Waldhober 2011), the UK (Reiner et al 2006a), the US (Curry et al 2005;Palmgren et al 2004;Reiner et al 2006b;), Switzerland (Wallquist, Visschers, and Siegrist 2009) and Sweden (Reiner et al 2006a) When engaged on the topic of CCS, community members tend to share similar concerns regarding the technology. Some fear that CO 2 may leak out of the storage site or during transportation, put water sources at risk or hurt property values .…”
Section: Ccs and Industry-community Relationsmentioning
confidence: 97%
“…Third, in a country with previous political conflicts over similar issues there is a greater risk that CCS may re-activate old conflict lines and resistance than in one with no such political conflicts (Fischedick 2009). This is difficult to establish objectively, but we asked interviewees to reflect on relevant potential or real issue linkages, leaving them to make connections.…”
Section: Analytical Frameworkmentioning
confidence: 99%